Female Crime and Delinquency: A Kaleidoscope of Changes at the Intersection of Gender and Age - Carvalho, Maria João Leote de (Women & criminal justice, 2023)
This article discusses the role that gender and age play in female crime and delinquency in Portugal, drawing on the voices of female offenders across different generations—childhood, youth, and adulthood. Based on the analysis of 49 interviews with female offenders, it explores the ways in which these girls and women construct and account for their own criminal behavior. The results reveal a kaleidoscope of changes cutting across generational groups, punctuated by increasing involvement of younger groups in offending as a form of emancipation. Young and older female offenders show different patterns of offending, which reflect multiple and ambivalent old and new forms of femininity. Girls’ and women’s paths both to and in offending have their own idiosyncrasies. They also reflect the way gender is being constantly reconfigured and reconstructed through time, and in different social and institutional contexts.